A questão criminal neoliberal : entrelaces entre a racionalidade hegemônica e punição - Santos, Jádia Larissa Timm dos (2022)
Nowadays, one understands neoliberalism as a hegemonic rationality that shapes subjectivities. So, it is not just an economic theory. Having it spread to all areas of society and government, thinking about the criminal issue implies discovering to what extent neoliberalism also applies to it. Therefore, the main object of this work is the neoliberal penalty. And the research problem is this: How neoliberal hegemonic rationality is reflected in the contemporary quaestio criminalis? To answer that, one seeks the origins, theories, ideas, and thinkers that contributed to the formation of neoliberalism even before its creation. Thus, what one analyzes in current times is not something completely new, representing an annulment of the past. It is the result of a movement, of a process, that comes from a few centuries ago. The same ought to be argued about the neoliberal penalty. The research has a three-part structure. The first goes deep into the origins of what today translates as neoliberalism and punishment as economic rationality. The second part unfolds neoliberalism from its “cradle”. In sequence, one describes the neoliberalism implementation process and characterizes it to the present day. Then, one entangles neoliberalism with other phenomena and facets, such as neoconservatism and authoritarianism. In the third part of the work, one analyzes the Chicago school economic theory of law and, specifically, of crime in order to arrive at the neoliberal penalty theory. In the final part, the central theoretical reference is the work of Bernard E. Harcourt, especially his view of the neoliberal penalty theory. Nevertheless, one cites many other authors working from the perspective of the demand for order in economic and social structures. The thesis stands for not considering the neoliberal penalty outdated, as it should perform as an umbrella concept. Moreover, one proposes an extension of the neoliberal penality concept, merging it with neoconservatism. Such an alliance contributes to increasing the punitive arm of the state in points that neoliberalism alone would not be able to.